Cu Anchored Ti2NO2 as High Performance Electrocatalyst for Oxygen Evolution Reaction: A Density Functional Theory Study. Issue 16 (22nd June 2020) - Chen, Zhiguo; Fan, Xiaoli; Shen, Zihan; Ruan, Xiaopeng; Wang, Lan; Zeng, Hanghang; Wang, Jiahui; An, Yurong; Hu, Yan
Abstract: MXenes have attracted great attention in the fields of energy conversion and catalysis, and have proved to be an effective supporting material for single atom catalysts (SACs). In the present study, we investigated the catalytic activity of a series mono‐atomic transition‐metal atoms supported by MXenes M2 NO2 for oxygen evolution reaction (OER) via first principle calculation. Particularly, single atom Cu site on Ti2 NO2 having the lowest overpotentials of 0.24 V and bonding with the reaction intermediates moderately, is the most active SAC for OER. Energetically, Cu atom prefers to be mono‐atomically anchored on Ti2 NO2 instead of aggregating. Plus, Cu anchoring enhance the electronic states around Fermi level. Additionally, ab‐initio molecular dynamics simulations show that Cu atom is anchored on Ti2 NO2, stable and isolatable at 300 K. Studies on the small molecule adsorption on Cu‐Ti2 NO2 further prove the potential applications of Cu−Ti2 NO2 as active SACs for OER. Our results broaden the perception of MXenes and guide the exploration of non‐noble metal based OER electrocatalysts. Abstract : Oxygen evolution reaction : In this work, we explore a series of single transition‐metal atoms anchored MXenes M2 NO2 (M=Ti, V, Cr) as OER electrocatalyst. Among them, Cu‐Ti2 NO2 is predicted to be the best potential candidate with low overpotential (0.24 V), high conductivity, and durable stability. At the same time, our calculations verify that the composited descriptor ζ which closely relates to intrinsic properties of materials can be an efficient principle to search new catalysts. We hope our works provide inspiration for designing new generation OER electrocatalysts.